دور جدول حسابات النتائج في تحليل الوضعية المالية للمؤسسة الإقتصادية دراسة حالة مؤسسة إتصالات الجزائر بالأغواط - مخلوفي أسماء; الياقوت نوقبة; بوهالي خيرة (جامعة عمار ثليجي الاغواط, 2022)
The purpose of the study was to analyze Income statement for the reason of analyzing the financial position of the economic enterprise, so that we got recognized with the numerous theoretical aspects of the Income statement and financial analysis likewise to the techniques and relative indicators used in analyzing the Income statement. An Empirical Study was conducted on the Algeria Telecom enterprise in Laghouat, through the application of techniques and indicators to analyze the Income statement. via this study, we concluded that the financial position of the enterprise has deteriorated somewhat, and this is due to the large number of burdens and expenses incurred by the Corporation, which made it achieve successive losses. Which requires them to take appropriate corrective action.